2010
DOI: 10.1002/jcp.22226
|View full text |Cite
|
Sign up to set email alerts
|

12‐O‐tetradecanoylphorbol‐13‐acetate‐induced invasion/migration of glioblastoma cells through activating PKCα/ERK/NF‐κB‐dependent MMP‐9 expression

Abstract: An increase in MMP-9 gene expression and enzyme activity with stimulating the migration of GBM8401 glioma cells via wound healing assay by 12-O-tetradecanoylphorbol-13-acetate (TPA) was detected in glioblastoma cells GBM8401. TPA-induced translocation of protein kinase C (PKC)alpha from the cytosol to membranes, and migration of GBM8401 elicited by TPA was suppressed by adding the PKCalpha inhibitors, GF109203X and H7. Activation of extracellular signal-regulated kinase (ERK) and c-Jun-N-terminal kinase (JNK) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
73
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 86 publications
(76 citation statements)
references
References 46 publications
(42 reference statements)
2
73
1
Order By: Relevance
“…TPA was found to significantly enhance cell migration abilities of human cancer cells including hepatoma and breast cancer cells (18,19). In addition, TPA-induced migration and invasion of glioblastoma cells were prevented by blocking PKCα-dependent pathways (20). Consistent with these reports, we found that TPA increased cell migration in thyroid and breast cancer cells.…”
Section: Discussionsupporting
confidence: 90%
“…TPA was found to significantly enhance cell migration abilities of human cancer cells including hepatoma and breast cancer cells (18,19). In addition, TPA-induced migration and invasion of glioblastoma cells were prevented by blocking PKCα-dependent pathways (20). Consistent with these reports, we found that TPA increased cell migration in thyroid and breast cancer cells.…”
Section: Discussionsupporting
confidence: 90%
“…Although suppression of MMP-9 expression by kaempferol, quercetin, and morin was reported in different conditions Lee et al, 2013;Lin et al, 2010;Sivaramakrishnan and Niranjali Devaraj, 2009;Yi et al, 2012), our study showed that MMP-9 secretion from HT-1080 cells was severely decreased by galangin as well as kaempferol, and moderately decreased by fisetin. Interestingly, quercetin weakly affected and morin did not affect MMP-9 secretion.…”
Section: Discussioncontrasting
confidence: 56%
“…In addition MMP inhibition, it has recently been shown that flavonols can regulate MMP function through transcriptional suppression. For example, kaempferol suppresses PMA-induced MMP-9 expression in glioblastoma GBM8401 cells (Lin et al, 2010), MMP-2 expression in tongue squamous cell carcinoma SCC4 cells , and MMP-2 and MMP-9 expression in human osteosarcoma U-2 OS cells . Quercetin downregulates oxidized LDL-induced expression of MMP-1, MMP-2, and MMP-9 in human umbilical vein endothelial EA.hy926 cells (Yi et Cells were starved for 24 h, preincubated for 30 min with 30 M of galangin, kaempferol, or gossypetin (as a negative control), and stimulated for 30 min with 30 ng/ml PMA.…”
Section: Discussionmentioning
confidence: 99%
“…Once triggered, these proteins can activate and interact with other cascades such as MAPK and PI3K, and regulate processes such as proliferation, differentiation, apoptosis, and angiogenesis [110,111] . These events make PKC an important target in cancer, particularly in glioma where its importance has been thoroughly discussed [112][113][114] as PKC shows increased expression and activity in this kind of tumors [115] . There are reports indicating that PKC is important for progesterone-receptor-mediated proliferation in glioma cells, adding to the possible mechanisms of PKC function [114] .…”
Section: Protein Kinase C (Pkc)mentioning
confidence: 99%
“…The importance of PKC in therapy resistance has been highlighted, particularly PKC's implication in cell cycle regulation [116] . PKCα activates MAPK and MMP, thus increasing infiltration ability [112] ; PKCδ has been linked to radiation-induced apoptosis as well as MMP activation [119,120] ; and PKCε induces proliferation and apoptosis evasion [121] . Moreover, our group has reported that PKCα and PKCδ, through progesterone receptor phosphorylation, induce proliferation and migration [114] .…”
Section: Protein Kinase C (Pkc)mentioning
confidence: 99%